Secure network coding method merged with timestamp and homomorphic signature - Heng-li PEI; Tao SHANG; Jian-wei LIU (Tongxin xuebao)
A secure network coding method merged with timestamp and homomorphic signature which can solve security issues in wireless multi-hop networks was proposed.The timestamp into RSA-based homomorphic signature scheme was brought and used to produce random coefficients of net it possible to defend pollution attacks and replay attacks simultaneously while maintaining the homomorphic property of the signature.The analysis that mainly focus on was the influence of random coefficients on decoding probability of network coding a security of the proposed scheme.Results indicate that the proposed scheme can defend pollution attacks and replay attacks simultaneously,and the ratio of overhead between RSA-based homomorphic signature scheme and the proposed scheme is approximates 1.